2019
DOI: 10.1016/j.ejvs.2019.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved Venous Allografts in Supra-inguinal Reconstructions: A Single Centre Experience

Abstract: WHAT THIS PAPER ADDS The current study introduces arterial reconstructions with cryopreserved femoral and vena caval vein allografts as a novel technique in the supra-inguinal setting with a low rate of re-infections and acceptable number of graft re-interventions on mid term analysis. Objective: This study introduces a novel technique for supra-inguinal arterial reconstructions with cryopreserved femoral vein and caval allografts with a low re-infection rate and an acceptable graft re-intervention rate on ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
(43 reference statements)
0
9
0
1
Order By: Relevance
“…25,26 Other possibilities involve the use of cryopreserved arterial and venous allografts, where especially the latter seems like a viable option, particularly in cases where the deep veins are unsuitable. 27 However, cryopreserved grafts are not readily accessible for most vascular centres and dedicated cryopreservation programmes are currently only available in two Swedish university hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Other possibilities involve the use of cryopreserved arterial and venous allografts, where especially the latter seems like a viable option, particularly in cases where the deep veins are unsuitable. 27 However, cryopreserved grafts are not readily accessible for most vascular centres and dedicated cryopreservation programmes are currently only available in two Swedish university hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 23 supra-inguinal arterial reconstructions using cryopreserved venous allografts -5 of which were mycotic AAAsgraft reinfection occurred in only one patient and two required reintervention for anastomotic dilatation. 24 This is a similarly J o u r n a l P r e -p r o o f low rate of reinfection as found in the largest study of cryopreserved arterial allografts for aortic reconstruction, which reported reinfection in 8 of 220 (4%) of cases. 25 The use of cryopreserved vein in this setting remains uncommon; among 56 mycotic AAAs in a multicentre study of all cases across six countries from 2006-2016, only two procedures used cryopreserved venous allografts.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 56%
“…1,3 Furthermore, we have our own homograft bank at Helsinki University Hospital, where we cryopreserve mostly femoral veins obtained from cadavers to be used in oncovascular procedures to replace resected larger vessels. 4 While endovascular surgery has taken over the field of aortic surgery for occlusive disease and aneurysms, oncovascular surgery still requires true open surgery. As typical aortic procedures have decreased dramatically as a result of the endovascular "tsunami", teaching aortic surgery to trainees has become more difficult.…”
mentioning
confidence: 99%